Photoletter to the editor: Dermoscopy of atypical lichen sclerosus involving the tongue - Apalla, Zoe (Specjalisci Dermatolodzy, 2012)
Involvement of tongue during the course of lichen sclerosus is extremely rare, with only five – to our knowledge – described cases in the English literature. We present clinical and dermoscopic findings of a female patient who concomitantly developed genital, skin and oral lesions of lichen sclerosus. Tongue involvement consisted of a linear atrophic whitish plaque, strikingly mimicking "en coupe de sabre" scleroderma. Dermoscopic examination revealed a well demarcated, linear, dense, white, homogenous area, with papillae projections hardly seen in the affected area. Dermoscopy of lesions located on the trunk revealed whitish plaques with comedo-like openings in the center and an erythematous halo at the periphery. Since clinical differentiation of oral LS and other oral diseases appearing as white atrophic plaques is almost impossible without using histology, we believe that dermoscopy might represent an additional tool, contributing to the final diagnosis, and thus avoiding an ablative procedure at this site-sensitive localization.